THE DISEASE INTENSITY AND INCIDENCE OF BLACK SIGA-TOKA ON BANANA (Musa paradisiaca) IN KARANG BENDO, BANGUNTAPAN DISTRICT, BANTUL REGENCY, SPECIAL REGION OF YOGYAKARTA - Najwa Meutia Nisa; Muhammad Luthfi Shiddiq; Michael William Axl (Agrofarm: Jurnal Agroteknologi, 2026)
Banana (Musa paradisiaca) is one of the most important commodities for food security and local economy, particularly in Indonesia. However, banana productivity is threatened by several major biotic stress factors, including insect pests and fungal diseases. The present study was conducted in Karang Bendo, Banguntapan District, Bantul Regency, aiming to identify the presence and impact of major banana pests and diseases, namely Black Sigatoka disease. Field surveys were carried out using the Simple Random Sampling method, with observations on symptoms of infestation and infection on leaves, pseudostems, and corms. Data analysis was performed using descriptive statistics and ANOVA to determine infestation intensity. The results showed that Black Sigatoka (Pseudocercospora fijiensis) resulted in leaf spotting, reduced fruit shelf life, and increased control costs. Overall, these pests and diseases significantly affect banana growth, yield, and plantation longevity. Integrated pest and disease management strategies based on accurate field identification are required to reduce production losses and support sustainable banana cultivation.